Enhancing the deployment of solar energy in Norwegian high-sensitive built environments: challenges and barriers—a scoping review - Akbarinejad, Tahmineh; Machlein, Esther; Bertolin, Chiara; Lobaccaro, Gabriele; Salaj, Alenka Temeljotov (Frontiers in Built Environment, 2023)
Heritage and historical buildings often face climate vulnerabilities, decay of technical performance and energy inefficiency that threaten their use and consequently their long-term preservation. Due to urban densification and escalating energy consumption, addressing these vulnerabilities is crucial to protect, rehabilitate and keeping in use historical buildings in cities and utilizing renewable energy sources like solar energy should have a pivotal role towards sustainable cities and communities. However, integrating solar technology into historical buildings faces unique challenges mainly because of the significance, non-standard construction methods adopted, and the valuable original materials. Norway, with its Climate Action Plan and a substantial portion of cultural historic buildings in its building stock, aims to significantly reduce emissions and is seeking for novel solutions. This paper discusses challenges and barriers associated with adoption of solar energy in high-sensitive built environment in Norway, through a scoping review. The results outline conservation criteria as challenges, which include viability, feasibility, integration, reversibility, compatibility, reliability and safety, noninvasiveness, and acceptability. Additionally, the review identifies barriers such as economic, geographic, technical, conservative, legislative, and social factors. Initially, the frequency with which these challenges and barriers appear in academic papers is examined. Subsequently, the interconnections between these challenges and barriers are explored to assess their specific impacts within the Norwegian context. Recognizing these challenges and understanding their interconnection can represent the strength of the relationship between them and can allow to identify potential solutions and strategies to support stakeholders, experts, or public authorities for successfully implementation and integration of solar energy systems in high-sensitive built environments in the future.